PENGARUH DIRASAH DI PESANTREN TERHADAP MANAJEMEN PEMBELAJARAN MAHASISWA - Rofik, Mochamad (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2022)
The purpose of this study was to determine the learning management of students at STIKES Surya Global Yogyakarta. The method used in this study is a quantitative method with 66 samples. The results of the R2 test in this study were 0.39 or 39%. This means that the magnitude of the influence of the dirÄsah variable on the learning management of students at the Surya Global School of Health Sciences (STIKES) of Surya Global Yogyakarta is 39%, while the remaining 61% (100% - 39%) must be explained by other causal factors. The result of t count shows t count > t table (13,193 > 2,52); There is a significant influence between dirÄsah on the learning management of students at Surya Global School of Health Sciences (STIKES) Yogyakarta.